Analysis on Flexural Capacity of Square Steel Tube Truss Concrete Beams with Grouted Chords - Kun Wang; Zhiyu Zhu; Huihui Luo; Ahmed Ahmad Omar (Advances in Materials Science and Engineering)
In this research paper, simulations on five specimens of square steel tube truss concrete beams with grouted chords were conducted by finite element analysis (FEA) software ABAQUS. Comparison of failure modes, vertical load-deflection curves, and steel tube strain variation with tests was done. The rationality and validity of the FEA models were also verified. On this basis, parameter analysis was carried out, and the influence of concrete strength, steel ratio of upper and lower chords, and spacing of steel tube truss joints on the vertical load-deflection curves were obtained. From the results of tests and parameter analysis, design formulae of flexural bearing capacity for composite beams were proposed based on the assumption that steel tubes are equivalent to ordinary longitudinal steel bars. Accordingly, the results indicated that the steel tubes of the upper chords in the composite beams cannot get yield for full sections due to the structural requirements; the steel tube of the lower chords will be the first to reach fully yielding and the upper concrete crushed subsequently, showing a failure mode analogous to that of the under-reinforced concrete beam; the steel ratio of lower chords is the primary factor affecting the flexural capacity of the normal section among the parameters; the calculation from the proposed design formulae for the flexural capacity of normal section is in agreement with the tests and simulations. This research could provide reference for the design of this kind of composite beam.